1994
DOI: 10.1128/aac.38.7.1519
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ceftriaxone during plasma exchange in polyarteritis nodosa patients

Abstract: Plasma exchange (PE) is currently being used to treat a variety of disorders involving immune complexes, such as polyarteritis nodosa. This procedure removes endogenous toxic components that accumulate in patients with this disease, but it also removes drugs. Plasma-protein binding and the volume of distribution (V) are two kinetic parameters which strongly affect the efficiency of drug removal by PE. Drugs that are highly bound to plasma proteins and have a low V may show a marked decrease in plasma levels as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…(13) advocated this parameter as the one with the most influence on compounds’ removal, taking precedence over protein binding and V d . This was supported by investigations noting an increased amount of drug removed when TPE was started immediately (teiclopenin [19], ceftriaxone [20]) or shortly (ceftazidime [21], phenobarbital [22]) after dose administration. Clinical observations corroborate these findings.…”
Section: Tpe Influence On Drug Dispositionmentioning
confidence: 92%
“…(13) advocated this parameter as the one with the most influence on compounds’ removal, taking precedence over protein binding and V d . This was supported by investigations noting an increased amount of drug removed when TPE was started immediately (teiclopenin [19], ceftriaxone [20]) or shortly (ceftazidime [21], phenobarbital [22]) after dose administration. Clinical observations corroborate these findings.…”
Section: Tpe Influence On Drug Dispositionmentioning
confidence: 92%
“…Other studies on ␤-lactam antibiotics indicate that protein binding of the antibiotic is the important factor determining antibiotic removal. The third-generation cephalosporin ceftriaxone has a low V d and high protein binding and has been shown to be significantly removed by PE [19,20], whereas ceftazidime, another third-generation cephalosporin that has a low V d but low protein binding, has been shown not to be significantly affected by PE [21]. Given the data from this case, continuous infusion of ␤-lactam antibiotics should be encouraged in hospitalised patients receiving PE.…”
Section: Discussionmentioning
confidence: 75%
“…To ensure anticoagulation, citrate (pH 5.0±0.5) was given in a 1:10 v/v ratio with blood. Citrate has no effect on the protein binding of drugs [5]. Every patient underwent 14 sessions of plasma exchange over 3 weeks, and hemostasis was assessed before and after each session.…”
Section: Methodsmentioning
confidence: 99%
“…whereas Prince et al [3] reported a 35% decrease in plasma concentration of gentamicin compared to the initial level in newborns. β‐lactam elimination during plasma exchange has been the subject of four investigations: Prince et al [3] found that circulating ampicillin concentrations dropped by 35%; Bozkurt et al [1] noted that ceftazidime elimination varied from 2% to 9% depending on whether the patient had renal insufficiency; and Bakken et al [4] and Fauvelle et al [5] observed that the fraction of ceftriaxone eliminated reached 6–12% and 11.5–24% respectively, depending upon the time lapse between drug administration and the onset of plasma exchange. The influence of plasma exchange on the elimination of glycopeptides is unknown.…”
Section: Introductionmentioning
confidence: 99%